Predicted Loop Regions Promote Aggregation: A Study of Amyloidogenic Domains in the Functional Amyloid FapC. Issue 7 (27th March 2020) - Nagaraj, Madhu; Ahmed, Mumdooh; Lyngsø, Jeppe; Vad, Brian Stougaard; Bøggild, Andreas; Fillipsen, Anne; Pedersen, Jan Skov; Otzen, Daniel Erik; Akbey, Ümit
Abstract: Protein fibrillation is traditionally associated with misfolding, loss of functional phenotype, and gain of toxicity in neurodegenerative diseases. However, many organisms exploit fibrils in the form of functional amyloids (FA), as seen in bacteria, such as E. coli, Salmonella, Bacillus, and Pseudomonas. Here, we provide structural information and mechanistic data for fibrillation of the smallest amyloidogenic truncation unit along with the full-length version (FL) of the major amyloid protein FapC from Pseudomonas, predicted to consist of three β-hairpin-forming imperfect repeats separated by disordered regions. Using a series of truncation mutants, we establish that the putative loops (linkers) increase the rate of aggregation. The minimal aggregation unit consisting of a single repeat with flanking disordered regions (R3C) aggregates in a pathway dominated by secondary nucleation, in contrast to the primary nucleation favored by full-length (FL) FapC. SAXS on FapC FL, R3C, and remaining truncation constructs resolves two major coexisting species in the fibrillation process, namely pre-fibrillar loosely aggregated monomers, and cylindrical, elliptical cross-section fibrils. Solid-state NMR spectra identified rigid parts of the FapC fibril. We assigned Cα–Cβ chemical shifts, indicative of a predominant β-sheet topology with some α-helix or loop chemical shifts. Our work emphasizes the complex nature of FapC fibrillation. In addition, we are able to deduce the importance of non-repeat regions (i.e., predicted loops), which enhance the amyloid protein aggregation and their influence on the polymorphism of the fibril architecture. Graphical abstract: Image 1 Highlights: Predicted Loop Regions Promote FapC functional amyloid Aggregation. The minimal aggregation unit consisting of a single repeat with flanking disordered regions (R3C) aggregates via secondary nucleation, in contrast to the primary nucleation favored by full-length (FL) FapC. Small-angle X-ray scattering (SAXS) on FapC FL, R3C, and remaining truncation constructs resolve two major coexisting species in the fibrillation process. Solid-state NMR spectra identified rigid parts of the FapC fibril. We assigned Cα-Cβ chemical shifts indicating predominant β-sheet topology, with some α-helix or loop chemical shifts. The mobile forms/regions of FapC were identified by INEPT NMR experiments.